Komunikasi Antar Budaya Pasangan Kawin Campur di Indonesia - Budyanto, Chrestella; Sari, Marchelia Pamela; Diamanta, Nadhira Puspa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
As the world opens up and multicultural interactions increases, the same applies to intercultural relationships. In Indonesia, especially in the capital of Jakarta, people from different backgrounds of culture even countries are often met and some, fall in love. The study aims to understand and discover how individuals married to someone who is from different culture live, and the process of intercultural communication happen in an intimate relationship of a marriage. The study uses qualitative methodology with interpretive paradigm. The result of the study shows intercultural marriages comes with just as many conflicts as in a monoculture marriage, but requires extra patience due to the different basic perspectives in approaching conflicts, and takes more time to adapt for the culture to assimilate to each other's. As the world opens up and multicultural interactions increases, the same applies to intercultural relationships. In Indonesia, especially in the capital of Jakarta, people from different backgrounds of culture even countries are often met and some, fall in love. The study aims to understand and discover how individuals married to someone who is from different culture live, and the process of intercultural communication happen in an intimate relationship of a marriage. The study uses qualitative methodology with interpretive paradigm. The result of the study shows intercultural marriages comes with just as many conflicts as in a monoculture marriage, but requires extra patience due to the different basic perspectives in approaching conflicts, and takes more time to adapt for the culture to assimilate to each other's.